UPAYA MENINGKATKAN KINERJA GURU KELAS V SD NEGERI 11 KESIMAN DALAM KEGIATAN BELAJAR MENGAJAR MELALUI SUPERVISI KLINIS - Sukarmiati, Ni Ketut (GUNA WIDYA: JURNAL PENDIDIKAN HINDU, 2019)
This School Action Research (PTS) discusses Clinical Supervision. The subject of this study was 1 (one) elementary school teacher / homeroom teacher named Komang Yanthi Trisna Dewi, S.Pd. SD. The selection of subjects was determined using purposive sampling technique, namely the technique of selecting data sources with certain considerations. The purpose of this study is to: (1) know the steps of Clinical Supervision on Class V teachers of SD Negeri 11 Kesiman; and (2) describe the improvement in the performance of Class V teachers in teaching and learning activities using Clinical Supervision. Data collection techniques are carried out, namely through observation, interviews, and documentation. The design of this study is a cycle model that is carried out repeatedly and continuously through two cycles, each cycle includes the process of the initial meeting or planning, the process of observation / observation carefully, and the process of reflection / analyzing the results of observations and providing feedback. The hypothesis was analyzed using descriptive methods with percentage techniques. The steps of data analysis using Interactive Analysis, include: data collection, data reduction, data presentation, and conclusion or verification. The results of the school action research show that clinical supervision is carried out systematically and its application has succeeded in improving the performance of Class V teachers in teaching and learning activities using the Cooperative Learning Model. The final score achieved during the two cycles in the preparation of planning, implementation and also the assessment / follow-up of learning outcomes in teaching and learning activities is in the category of Good (80% - 89%). This means that the better clinical supervision is done, the higher the performance of Class V teachers in teaching and learning activities.